A New Complex of Curcumin with Sulfobutylether‐β‐Cyclodextrin: Characterization Studies and In Vitro Evaluation of Cytotoxic and Antioxidant Activity on HepG‐2 Cells. Issue 12 (9th October 2014) - Cutrignelli, Annalisa; Lopedota, Angela; Denora, Nunzio; Iacobazzi, Rosa Maria; Fanizza, Elisabetta; Laquintana, Valentino; Perrone, Mara; Maggi, Vito; Franco, Massimo
<x xml:space="preserve">Abstract</x> Curcumin (CR) is a natural polyphenol with antioxidative, anti‐inflammatory, and anticancer properties but its therapeutic potential is substantially hindered by the rather low‐water solubility and bioavailability. Thus, in this work, a new soluble inclusion complex of CR with sulfobutylether‐β‐cyclodextrin (SBE‐β‐CD) was prepared in solution and at the solid state using different preparation techniques and characterized by Fourier transform infrared, nuclear magnetic resonance, differential scanning calorimetry, scanning electron microscopy, phase solubility studies, and Job's plot method. Results clearly indicate that CR reacts with SBE‐β‐CD to form a host–guest complex with an apparent formation constant of 1455 M−1. Moreover, SBE‐β‐CD strongly increases water solubility of CR (from 0.56 to 102.78 μg/mL, at 25°C), and lyophilization method seems to be the best preparation technique to obtain the complex at the solid state. Finally, an in vitro test on a human hepatic cancer cell line (HepG‐2) shows that complexation positively influences CR anticancer and antioxidant activity. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3932–3940, 2014